THE INFLUENCE OF PEER EDITING ONLINE TOWARDS THE STUDENTS’ WRITING SKILL - Akhmad Sutiyono; Destia Herlisya; Elvira Agape (JETA (Journal of English Teaching and Applied Linguistic), 2021)
Lots of students find the difficulties when they have to put their thoughts into writing. Moreover, when they need to do the proofreading and editing their own writing, this inevitably makes writing exceptionally tiring and distressing. In this study, researchers focused on a series of writing processes, especially editing and proofreading activities. The objective of this research was to find out the influence of Peer Editing online technique towards the students’ research proposal writing skill and to know and to describe whether the effectiveness of the students’ research proposal writing skill who learn through peer editing online is higher than those who learn through conventional technique. The research was conducted by using a quasi-experimental design with pretest and post-test. The population of this research are the students at the fifth semester of English education major at STKIP PGRI Bandar Lampung that consisted of 63 students in 2 classes. The sample of this research were two classes, they were as control class and experimental class. Control class was taught by Individual writing while experimental class was taught by peer editing online technique. In getting the data, the researchers used writing test. The result showed that based on the calculation, the researchers got that = 5.41 and = 2.00 and 2.66. It means that Ho is rejected and Ha is accepted. From the result above, the researchers state that there is an improvement and a significant influence of Peer editing online technique towards students’ research proposal writing skill.